Quadruplicate Synchronous Adenocarcinoma of the Colon with Distant Metastases—Long-Term Molecular Follow-Up by KRAS and TP53 Mutational Profiling - Bádon, Emese Sarolta (Diagnostics (Basel), 2020)
Anatomically independent tumor foci represent biologically distinct neoplasias, potentially featured by different progressivity and treatment responsiveness. To demonstrate the biological complexity, a metastatic colon adenocarcinoma patient originally presenting with four independent primary tumors of the right colon half and altogether eight distant metastases was followed by molecular testing. Next-generation sequencing results highlighted the mutational profile of the individual primaries and the dynamics of the different gene variants observed during follow-up. The four primary colon tumors presented with four different KRAS genotypes, one of them with a wild-type and three with pathogenic variants, without overlap. These were the following: c.35G > A; p.Gly12Asp with 40.6% variant allele frequency (VAF); c.34G > T; p.Gly12Cys with 16.2% VAF and c.35G > T; p.Gly12Val with 15.1% VAF. In metastatic tumors, with one exception where no mutation was detected, only the KRAS c.34G > T; p.Gly12Cys mutation could be detected. TP53 gene variants were variable in the primary tumors, with a single dominant variant evolving in the follow-up metastases (c.820G > T; p.Val274Phe). Genetic profiling of individually developing synchronous malignancies uncovers the clonal relations of metastatic tumors. NGS gene panels provide a solution to follow the dynamics of key oncogene variants during the course of the disease and greatly contribute to therapy optimization.